Cost Benefit Analysis (CBA) Program Pemberian Makanan Tambahan (PMT) Susu Pada Karyawan di PT. Trisula Textile Industries Tbk Cimahi Tahun 2018 - Rahmiyati, Ayu Laili (UI Scholars Hub, 2018)
Cost Benefit Analysis (CBA) for the process of identification , measurement,comparison social benefits and cost project or investment program to evaluate utilization of scarce economic resources so that it can be used efficiently .This research purposes are calculateing benefits and cost in rupiah from the milk supplementary feeding program (PMT) at PT. Trisula Textile Industries Tbk Year 2018 and deciding feasibility of program or policy sustainability from PMT milk. The research is using quantitative approach. Data collection is done through interviews, observations, and study documents. Calculation is using Payback Period (PP), Net Present Value (NPV), Internal Rate Of Return (IRR), and Benefit Cost Rate (BCR). The result showscalculation of NPV value on milk PMT program obtained results end Rp. 23,534,448,76, -. To conclude, the milk PMT program is acceptable because NPV> 0. Benefit-cost ratio , is 2.50 (≥ 1), meaning the milk PMT program is feasible. PT. Trisula Textile Industries Tbk is expected to continue the program of milk PMT. Basic research data could be used for preparing health program or health enhancement for employees through PMT or the other priority programs.